Smart cities in Russia: Technological innovations and urban transformations - Neshcheret Alexander; Nurova Oksana; Skornichenko Natalia; Oruch Tatiana (BIO Web of Conferences)
Our paper focuses on the technological innovations and urban transformations driving the development of smart cities in Russia. Smart cities, leveraging advancements like artificial intelligence (AI), the Internet of Things (IoT), and smart infrastructure, are reshaping urban management and enhancing citizens' quality of life. In order to face the worldwide trends, the Russian government has integrated smart city initiatives into national strategies such as the “Digital Economy of the Russian Federation,” targeting urban issues from transportation to environmental sustainability. Our paper demonstrates that many Russian cities serve as pioneering examples, with developments ranging from intelligent traffic management systems to digital twins and smart grids. AI plays a crucial role in managing urban systems, improving transportation, public safety, and resource distribution. Moreover, our results show that the implementation of smart grids and energy-efficient technologies highlights Russia's commitment to sustainability. This paper explains and summarizes how these innovations contribute to making Russian cities more efficient, connected, and resilient while positioning the country as a significant player in the global smart city movement. Our results might be of special interest for modern urban planners and city stakeholders as well as for researchers specializing in sustainable urban technologies.